THE EFFECT OF USING GRAPHIC ORGANIZER TO STUDENTS’ WRITING ABILITY - Kiki Juniarti; Dedi Sofyan; Kasmaini . (Journal of English Education and Teaching, 2017)
This study aimed at investigating the effect of using Graphic Organizer to students’ writing ability. This research was designed as a quasi-experimental research. The population of this research were all eleventh grade students at SMA N 1 Bengkulu Utara. The sample of this research was chosen by purposive sampling technique, so there were two science classes which consist of 52 students as the sample. Pre-test and post-test were involved as the instrument of this research. The first group was as experimental group taught by graphic organizer technique and the second group was as control group taught by conventional technique. The pre test was given to both experimental and control groups at the beginning, treatments were given in six meetings, and post test given at the end of the term. The data were analyzed by using t-test formula. From the calculation, the researcher found that the t-test value was 5.00, the degree of freedom value was 50, and the t-table was 3.49. Since t-test was higher than t-table (5.00 > 3.49), it meant that alternative hypothesis (H1) was accepted. Thus, it could be concluded that the use of graphic organizer was effective to students’ writing ability in term of content, organization, and language use.